The Effectiveness of Health Education Through Video Learning Multimedia On The Knowledge Of Youth About Menarche at SDN I Pakisaji - Ririn Harini; Fridha Luciana Andini (Jurnal Dedikasi, 2021)
Menarche (menar) is the first menstruation from the uterus which is the beginning of menstrual function and a sign of puberty in adolescent girls. In the last decade, there is a tendency for the menarche age to shift towards a younger age. (Williams and Wilkins, 2012).. Menars occurs in women of reproductive age between the ages of 10-16 years. What affects a woman to experience menarche is the maturity of the female reproductive organs. Nutritional status and stressors. Many problems are experienced by adolescents who experience menarche due to lack of knowledge about menarche, fear due to wrong information in dealing with menarche, and minimal information from teachers and parents (Andrijono, 2012). Researcher Septiana, 2016 in his research on the Relationship of Adolescent Knowledge with Nutritional Status, Physical Activity, and Age of Menarche. has recommended to provide information about menarche to the public, especially adolescents and to prepare mothers if their children experience early menarche. Research in Rome in 2003-2005 on knowledge and providing information about menarche in adolescents, the results obtained from 390 respondents 54.6% of them lack knowledge about menarche in adolescents (Pavia et al., 2006).